Recent Advances in Electrochemical and Optical Biosensors Designed for Detection of Interleukin 6 - Khan, Munezza Ata; Mujahid, Mohammad (Sensors (Basel, Switzerland), 2020)
Interleukin 6 (IL-6), being a major component of homeostasis, immunomodulation, and hematopoiesis, manifests multiple pathological conditions when upregulated in response to viral, microbial, carcinogenic, or autoimmune stimuli. High fidelity immunosensors offer real-time monitoring of IL-6 and facilitate early prognosis of life-threatening diseases. Different approaches to augment robustness and enhance overall performance of biosensors have been demonstrated over the past few years. Electrochemical- and fluorescence-based detection methods with integrated electronics have been subjects of intensive research due to their ability to offer a better signal-to-noise ratio, high specificity, ultra-sensitivity, and wide dynamic range. In this review, the pleiotropic role of IL-6 and its clinical significance is discussed in detail, followed by detection schemes devised so far for their quantitative analysis. A critical review on underlying signal amplification strategies and performance of electrochemical and optical biosensors is presented. In conclusion, we discuss the reliability and feasibility of the proposed detection technologies for commercial applications.